Creating thermal conductive pathways in polymer matrix by directional assembly of synergistic fillers assisted by electric fields. (November 2022) - Wu, Weifei; Ren, Tianli; Liu, Xueqing; Davis, Ryan; Huai, Kai; Cui, Xin; Wei, Huaixiao; Hu, Jinjin; Xia, Yuming; Huang, Shuohan; Qiang, Zhe; Fu, Kun (Kelvin); et al.
Abstract: Large amount of heat accumulated within the increasingly miniaturized electronic equipment negatively affects their device accuracy and service life, which can also cause potential environmental hazards and safety concerns. In this work, a strategy of creating thermal conductive pathways using micro-sized boron nitride (BN) and nano-sized alumina (Al2 O3 ) in polydimethylsiloxane (PDMS) matrix by the application of electric fields was demonstrated. The synergistic effect between two distinct particles enables the improved thermal conductivity of the BN/Al2 O3 /PDMS composites, which can be further enhanced by directional assembly of these fillers under electric fields. At the same filler loading content, the thermal conductivity of aligned ternary composite is 0.228 W/mK, which is higher than the random composites (0.215 W/mK), as well as their counterparts containing only a filler type (0.196 W/mK and 0.172 W/mK for BN/PDMS and Al2 O3 /PDMS composites, respectively). Furthermore, chain-like pathways from assembled fillers can improve the dielectric permittivity of the composites up to 6.6, while the dielectric loss remains at a low value (<0.1). Overall, this works provides a simple and effective strategy for manufacturing ternary polymer composites with improved thermal and dielectric properties through controlling the orientation of fillers. Graphical abstract: Image 1 Highlights: Efficient thermal conductive paths were created by the use of electric fields. The synergistic effects between BN and nano-sized Al2 O3 were enhanced through alignment microstructures. The aligned chain-structures not only enable the generation of more heat conduction paths but also can enhance the dielectric permittivity.